Co-curing preparation of flame retardant and smoke-suppressive epoxy resin with a novel phosphorus-containing ionic liquid. (January 2023) - Ou, Mingyu; Lian, Richeng; Cui, Jiahui; Guan, Haocun; Liu, Lei; Jiao, Chuanmei; Chen, Xilei
Abstract: Phosphorus-containing ionic liquid derivatives have been proven to be effective flame retardants for epoxy resin (EP). Flame retardants can accelerate the curing process and improve flame retardancy and smoke suppression of EP composites, which is challenging. In this paper, a novel phosphorus-containing ionic liquid (TPP-PF6 ) was synthesized and used both as a co-curing agent with 4, 4′-diaminodiphenylmethane (DDM) and as a highly effective flame retardant for EP. It has been found that TPP-PF6 was conducive to improve the char formation of EP to inhibit the smoke release at high temperatures. For EP/TPP-PF6 composites, the flame-retardant performance was enhanced rapidly with the increase of TPP-PF6 . With only 2 wt% of TPP-PF6, EP/2.0TPP-PF6 reached a UL-94 V-0 rating and a limiting oxygen index of 30.3%. The peak heat release rate, total heat release, and total smoke production values of EP/2.0TPP-PF6 were reduced by 36.32%, 45.81%, and 15.1% compared with those of pure EP, respectively. The thermal degradation products and flame retardant mechanism in gas and condensed phases were studied. It was found that TPP-PF6 had flame retardant effect in the barrier effect of the condensed phase and the quenching effect of the gas phase. This work explores the high-efficiency flame retardant and smoke-suppressive structures with co-curing properties for EP, thus promoting the wide application of EP materials. Graphical abstract: Image 1 Highlights: A phosphorus-containing ionic liquid (TPP-PF6 ) was successfully synthesized. TPP-PF6 was used as a co-curing agent, which can endow flame retardancy and smoke suppression tp EP. TPP-PF6 functioned in both condensed and gas phases because of its special chemical structure. A promising way to achieve co-curing behavior and flame retardancy was proposed.